Electrocoagulation for removal of chemical oxygen demand and heavy metals in leachate from Jeram sanitary landfill, Malaysia - Jotin, Rosie (2013)
The increasing amount of solid waste generation in Malaysia has become a problem in Solid Waste Management (SWM), since it creates serious impact to the environment especially on the landfill site. The generation of leachate during landfilling operation may impair environment by contaminating surface and ground water system either directly or indirectly from the site. Eventhough at a present most sanitary landfill is equipt with high level of leachate treatment facilities, leachate is still considered as a significant source of environmental pollution because their constituent that are difficult to be treated successfully. Therefore, innovative, cheap and effective techniques of purifying landfill leachate are needed before the leachate being discharged into water systems. The present study was conducted to investigate the efficiency of electrocoagulation processes in the removal of Chemical Oxygen Demand (COD) and heavy metals (Zn and Cu) from Jeram Sanitary Landfill leachate influenced by several parameters, thus proposing the optimum condition for pollutants removal. The electrocoagulation reaction was conducted in a batch reactor using aluminum as sacrificial electrodes. The effecting parameters such as applied voltage, conductivity and initial pH were studied to determine the condition of optimum removal. The variation of conductivity, pH and temperature also were noted during the electrocoagulation process. In this process, samples of 25 mL were taken out from the beaker at 10, 20, 40, 60, 80 and 100 minutes of electrolysis time. From the results obtained, the optimum operation conditions of the electrocoagulation process for the removal of COD, Zn and Cu was found to be as follows: applied voltage of 10 V 0=0.0207 m.A/cm"), conductivity of 28.00 mS/cm or lower, initial pH of 6 and 100 minuntes of electrolysis time. At these conditions, approximately, 61.86 % COD, 74.41 % Zn and 97.47 % Cu removals can be reached. In this study, the electrocoagulation process has proved to be effective in the removal of COD and heavy metals from sanitary landfill leachate.